Inflation in the United States, causes and consequences : proceedings ([New York] : Conference Board, 1974)
Experts on individual aspects of inflation - its causes, its consequences, the policy equipment with which we seek to restrain it, and the real and financial effects of the struggle against inflation - offer their views, and respond to the searching questions of their colleagues
osc 27/08/2021
Loans
Keywords: Inflation (Finance); United States; United States